2023
DOI: 10.3390/ijms24087433
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-146b-5p Suppresses Pro-Inflammatory Mediator Synthesis via Targeting TRAF6, IRAK1, and RELA in Lipopolysaccharide-Stimulated Human Dental Pulp Cells

Abstract: MicroRNA-146b-5p (miR-146b-5p) is up-regulated during and to suppress the inflammation process, although mechanisms involved in the action of miR-146b-5p have not been fully elucidated. This study examined the anti-inflammation effects of miR-146b-5p in lipopolysaccharide (LPS)-stimulated human dental pulp cells (hDPCs). An increase in human miR-146b-5p (hsa-miR-146b-5p) expression following the mRNA expression of pro-inflammatory cytokines was observed in LPS-stimulated hDPCs. The expression of hsa-miR-146b-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…These findings demonstrate miR-27a-5p as a negative regulator of proinflammatory cytokine synthesis, and it may act as a member of negative feedback loops. We have reported that miR-21 and miR-146b negatively regulate proinflammatory cytokine synthesis by targeting NF-κB in LPS-stimulated hDPCs 25,41 , and miR-27a-5p may be a negative regulator in pulpal inflammation. Excessive synthesis of proinflammatory cytokines leads to the destruction of homeostasis, which induces severe damage to host tissues 4244 .…”
Section: Discussionmentioning
confidence: 94%
“…These findings demonstrate miR-27a-5p as a negative regulator of proinflammatory cytokine synthesis, and it may act as a member of negative feedback loops. We have reported that miR-21 and miR-146b negatively regulate proinflammatory cytokine synthesis by targeting NF-κB in LPS-stimulated hDPCs 25,41 , and miR-27a-5p may be a negative regulator in pulpal inflammation. Excessive synthesis of proinflammatory cytokines leads to the destruction of homeostasis, which induces severe damage to host tissues 4244 .…”
Section: Discussionmentioning
confidence: 94%